ANALISIS NOTASI DDC 23 TABEL 5 ETNIK DAN KELOMPOK KEBANGSAAN : Studi Kasus Pengembangan Notasi T5-992 2 - Suharyanto Suharyanto (Perpustakaan Nasional RI, 2019)
Dewey Decimal Classification edition 23 was published in 2011. Among the new addition and features are Table 5 for ethnic expansion in Indonesia based on language speakers. On the other side, a survey by Central Statistical Board there are 29 ethnic groups which can be expanded into 1,128 ethnics. The authors propose that there should be more notation for ethnics and ethnic groups in Indonesia based on Central Statistical Agency for Indonesian needs.